It's about time ! : Jan Van Eyck Academie : Jaarboek 2007. - Jan van Eyck Akademie, Maastricht (Maastricht : Jan Van Eyck Akademie, 2008)
Barry, Orla ; Brüchner, Anke ; Cuomo, Raffaele ; Iorio, Maria ; Dijkman, Marjolijn ; Jacquerie, Thibaut ; Konrad, Aglaia ; Koolen, Rachel ; Lechleitner, Ines ; Lengerer, Achim ; Maitre, Jean-Baptiste ; Matthys, Kobe ; Meunier, Karolin ; Müller, Peter ; Querrec, Stephane ; Sachs, Hinrich ; Schmalisch, Romana ; Stidworthy, Imogen ; Sullivan, Megan
Nederlands
boek